2022
DOI: 10.3389/fnagi.2022.885393
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gut microbiota correlate with symptoms and regional brain volumes in patients with late-life depression

Abstract: Depression is associated with gut dysbiosis that disrupts a gut-brain bidirectional axis. Gray matter volume changes in cortical and subcortical structures, including prefrontal regions and the hippocampus, have also been noted in depressive disorders. However, the link between gut microbiota and brain structures in depressed patients remains elusive. Neuropsychiatric measures, stool samples, and structural brain images were collected from 36 patients with late-life depression (LLD) and 17 healthy controls. 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 81 publications
0
11
3
Order By: Relevance
“…The phenome evaluates the severity of the combination of several depressive features, and as a quantitative score, and provides more information than MDD, which is an incorrect model (see Introduction). Comparing the results of the present investigation conducted on Thai MDD patients with those of previous LefSe studies conducted in other cultures and nations reveals almost no agreement (Zhang et al 2022; Zhao et al, 2022; Ling et al, 2022; Liu et al, 2022; Jiang et al, 2015; Zhu et al, 2021; Painold et al, 2018; Tsai et al, 2022). Notably, the LefSe study published by Liu et al (2022) revealed a higher abundance of Clostridium in the control group, which is consistent with a lower abundance being related to the depressive phenome in the current study.…”
Section: Discussioncontrasting
confidence: 75%
“…The phenome evaluates the severity of the combination of several depressive features, and as a quantitative score, and provides more information than MDD, which is an incorrect model (see Introduction). Comparing the results of the present investigation conducted on Thai MDD patients with those of previous LefSe studies conducted in other cultures and nations reveals almost no agreement (Zhang et al 2022; Zhao et al, 2022; Ling et al, 2022; Liu et al, 2022; Jiang et al, 2015; Zhu et al, 2021; Painold et al, 2018; Tsai et al, 2022). Notably, the LefSe study published by Liu et al (2022) revealed a higher abundance of Clostridium in the control group, which is consistent with a lower abundance being related to the depressive phenome in the current study.…”
Section: Discussioncontrasting
confidence: 75%
“…Although this LEfSe analysis discovered numerous discriminative taxa at an LDA threshold of > 3, there were no parallels between our findings and those of Ling et al Moreover, whilst we discovered that Gemmiger and Desulfovibrio were abundant in controls, Ling et al [81] discovered the opposite. There are no similarities between our results (obtained in younger MDD patients and controls) and those of patients with late-life depression [82], despite the fact that the latter LEfSe analysis found many significant abundances of bacterial taxa at the genus level in controls as opposed to patients with late-life depression.…”
Section: Abundance Of Gut Microbiome Taxa In Mddcontrasting
confidence: 74%
“…Although this LefSe analysis discovered numerous discriminative taxa at an LDA threshold of > 3, there were no parallels between our findings and those of Ling et al Moreover, whilst we discovered that Gemmiger and Desulfovibrio were abundant in controls, Ling et al [82] discovered the opposite. There are no similarities between our results (obtained in younger MDD patients and controls) and those of patients with late-life depression [83], despite the fact that the latter LEfSe analysis found many significant abundances of bacterial taxa at the genus level in controls as opposed to patients with late-life depression.…”
Section: Abundance Of Gut Microbiome Taxa In Mddcontrasting
confidence: 74%